1995
DOI: 10.1161/01.hyp.25.5.928
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Peptides in Spontaneously Hypertensive and Normotensive Donryu Rats

Abstract: The renin-angiotensin system has been implicated in the pathogenesis of hypertension in spontaneously hypertensive rats (SHR). Given that SHR may have normal or suppressed plasma levels of renin and angiotensin peptides, we examined whether the tissue levels of angiotensin peptides are elevated in these rats. We measured angiotensin-(1-7) [Ang-(1-7)], Ang II, and Ang I in plasma, kidney, adrenal, heart, aorta, brown adipose tissue, lung, and brain of male SHR and normotensive Donryu rats at 6, 10, and 20 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 46 publications
5
60
1
Order By: Relevance
“…32,33 Moreover, the cardiovascular effects due to an increase in the half-life of Ang II could, over time, be indistinguishable from the effects due to elevated synthesis of Ang II. A decrease in Ang II degradation in the kidneys from young SHR would be consistent with observations that young SHR are hypersensitive to Ang II injected into the renal artery 20,21 and that kidneys of young SHR have normal 4 or elevated 7 Ang II levels with depressed or normal, respectively, plasma renin activity. On the other hand, the levels of Ang II within the kidney have been reported to be lower in adult SHR relative to normotensive rats.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…32,33 Moreover, the cardiovascular effects due to an increase in the half-life of Ang II could, over time, be indistinguishable from the effects due to elevated synthesis of Ang II. A decrease in Ang II degradation in the kidneys from young SHR would be consistent with observations that young SHR are hypersensitive to Ang II injected into the renal artery 20,21 and that kidneys of young SHR have normal 4 or elevated 7 Ang II levels with depressed or normal, respectively, plasma renin activity. On the other hand, the levels of Ang II within the kidney have been reported to be lower in adult SHR relative to normotensive rats.…”
supporting
confidence: 88%
“…1,2 On the other hand, plasma renin activity and plasma angiotensin II (Ang II) levels are not consistently elevated during any given stage of development in SHR. [3][4][5][6][7] Likewise, although plasma Ang II is elevated in stroke-prone SHR, plasma renin, angiotensinogen, and Ang II do not cosegregate with elevated blood pressure. 8,9 It is now recognized that the tissue levels of components of the RAS are more reliable indices of functional activity than are plasma levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma and tissue levels of Ang II appear similar in the SHR and normotensive control rats. 36 However, it is possible that local cellular increases in Ang II production contribute to an enhanced Ang II action in an autocrine/paracrine manner. Recent studies have shown that cultured vascular smooth muscle cells from SHRs are capable of generating Ang II, which leads to autocrine stimulation of AT 1 receptors, whereas Ang II production was undetectable in vascular smooth muscle cell cultures from WKY rats.…”
Section: Blood Pressure Of Shrs and Wky Ratsmentioning
confidence: 99%